Chapter Studies of Lithium-Oxygen Battery Electrodes by Energy- Dependent Full-Field Transmission Soft X-Ray Microscopy - Tonti, Dino (InTechOpen, 2017)
The employment of printing techniques as cost-effective methods to fabricate low cost, flexible, disposable and sustainable solar cells is intimately dependent on the substrate properties and the adequate electronic devices to be powered by them. Among such devices, there is currently a growing interest in the development of user-oriented and multipurpose systems for intelligent packaging or on-site medical diagnostics, which would greatly benefit from printable solar cells as their energy source for autonomous operation.